Non-invasive visualization of vein in geriatric patients - Parthasarathy; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Medical treatment requires access to veins, which is challenging in geriatric patients. As age goes, the skin loses tone and elasticity, becoming more prone, bruising, and fragile. Older patients experience several medical conditions and weakened immune systems in which excessive venous punctures are anxious. Thanks to a lack of subcutaneous material, the veins become less healthy. The NIR camera is used for vein pictures, and the MATLAB (MATLAB) program package for processing is used. The camera resolution for NIR amounts to approximately 1080 * 720, which picks up areas behind the skin in order to find the venas by means of a new approach to visualize the vein using the triangulation of the hand photos. The tips of the knuckle are used for standardizing photos and separating regions of concern from the view of veins.